Deviant and Ashamed: Queer Indigenous Subject Formation in the Age of Grindr - Can Aydin (Current Objectives of Postgraduate American Studies)
In my contribution, I analyze shame, specifically ‘queer shame’ as an affect in Billy Ray-Belcourt’s (Driftpile Cree) essay “Loneliness in the Age of Grindr” which is from his A History of My Brief Body (2020). I examine how the queer Indigenous subject is formed through shame by participating in contemporary queer digital hookup culture and then later interacting with the Canadian public health system due to the possibility of HIV infection. In the essay, shame functions as an identity-forming affect, which is internalized, sometimes embraced, and also shaped by outside influences.